MODEL FOR IDENTIFYING SEPARATIST TENDENCIES: A PRACTICAL AND THEORETICAL APPROACH - Голубовић, Марко; Petrović, Rajko; Saković, Radiša (Serbian political thought, 2024)
Looking at the evolutionary process from the original human community to the present day, people have constantly sought freedom. Thus far, the best organizational solution to achieve such a need has been found in the formation of the state, as the key guarantor of the collective's survival. However, there are numerous collectives that currently lack their own state, and their rights are partially or (not) fully recognized within another state. Many achieve their struggle for freedom through peaceful means, negotiating with official institutions or changing the entire state system in a democratic and legal manner. However, there are also groups that endanger the territorial integrity and sovereignty of their parent states, and in order to achieve their interests, use violent means, thereby threatening peace, stability, and security. The primary goal of this study is to develop a general model that might enable the identification of separatist tendencies in sensitive areas of the world, regardless of the form of state organization. Additionally, the application of the model will be demonstrated through the example of the Republic of Serbia, one of the states with experience in combating separatist tendencies.
Keywords: separatism; Republic of Serbia; Security; Challenges; Risks; Threats